General anesthesia for dental care management of a patient with epidermolysis bullosa: 24‐month follow‐up. (2nd March 2016) - Mello, Bianca Zeponi Fernandes; Neto, Natalino Lourenço; Kobayashi, Tatiana Yuriko; Mello, Marina Barbosa Almeida; Ambrosio, Eloá Cristina Passucci; Yaedú, Renato Yassutaka Faria; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
ABSTRACT: Epidermolysis bullosa comprises a group of uncommon skin‐related diseases, characterized by the formation of blisters on mucocutaneous regions occurring spontaneously, following a trauma, exposure to heat, or as a result of minimal mechanical trauma. The dental treatment of the patient with epidermolysis bullosa raises many questions and discussions, due to the difficulty of carrying out the procedures. This report aimed to detail the clinical considerations of the treatment under general anesthesia of a patient with epidermolysis bullosa. The extraction of all deciduous teeth under general anesthesia was recommended based on the clinical and radiographic examinations. At 24‐month follow‐up, the patient had great improvement in oral hygiene without new caries lesions. The patient has been followed‐up at every month for caries lesion prevention and permanent tooth development. The treatment under general anesthesia provided the ideal safe conditions and was beneficial for the patient.